The singer and the scribe : European ballad traditions and European ballad cultures - Bennett, Philip E.; Green, Richard Firth, 1943- (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2004)
The Singer and the Scribe brings together studies of the European ballad from the Middle Ages to the twentieth century by major authorities in the field and is of interest to students of European literature, popular traditions and folksong. It offers an original view of the development of the ballad by focusing on the interplay and interdependence of written and oral transmission, including studies of modern singers and their repertoires and of the role of the audience in generating a literary product which continues to live in performance. While using specific case studies the contributors systematically extend their reflections on the ballad as song and as poetry to draw broader conclusions. Covering the Hispanic world, including the Sephardic tradition, Scandinavia, The Netherlands, Greece, Russia, England and Scotland the essays also demonstrate the interconnections of a European tradition beyond national boundaries.